PENGARUH KEPERCAYAAN KONSUMEN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN KONSUMEN - BAIHAQI, MUHAMMAD (Jurnal Ilmu Manajemen (JIM), 2016)
This study is to analyze and discuss the influence of customer trust and corporate image on customer satisfaction in the Big Royal Branch Gresik. This study using 105 samples, the sampling method is nonprobability sampling and purposive sampling technique. The data collection is done by distributing questionnaires and the data were analyzed using multiple regression analysis using SPSS 16. This study shows that customer trust and corporate image significantly influence consumer satisfaction in Big Royal Branch Gresik. Keywords: customer trust, corporate image, customer satisfaction.